Causes and effects of delay in the construction project - Nurshapika Adila, Adnan (2018)
A timely completion of the construction project is a major criterion of the project success. Failure to complete the project on time will ultimately result in delay. The need to control the causes of delays during the construction process comes out when the number of delay project has been increase from time to time. Hence, it is essential to identify the causes of this problem from the early stage of the construction project. The objectives of this study are to identify the causes of delay in the construction industry, to identify the effects of delay in the construction industry and finally to assess the best method to improve the problem of delay in the construction industry. This study takes an integrated approach and attempts to analyse the impact of delay. A questionnaire survey was conducted to identify the causes and effect of delay from client, consultant and Construction Company. This study identified the most important causes of delay from a list of thirty four causes, seven effect that contribute to construction project delay and recommendation the method to improve project delay. The perspective of client, consultant, contractor, material, equipment and external related problem has been analysed and ranked based on Relative Important Index (RII). Based on the RII result, the highest top ten ranking on causes of delay have been produced. Client related has the highest contribution to causes of project delay in project by client inference during the construction project. The seven effect of delay were cost overrun, time overrun, interior quality of works, blacklisted by relevant authorities, loss of interest by stakeholders, non-payment by employer and rescheduling of works. ‘Cost overrun’ and ‘time overrun’ has been the main effect to the project causes by project delay.